Recontextualizing Empathy: Empowerment Communication of Caregivers in a Social Nursing Home Setting - Nela Rizqilillah; Deddy Mulyana; Yanti Setianti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2026)
The aging population phenomenon in Indonesia has led to an increasing need for long-term care services for the elderly, particularly within formal institutions such as social nursing homes. In this context, empathy is often understood as an affective response manifested as protection and total assistance from caregivers to the elderly. However, such an understanding has the potential to foster paternalistic relationships that may actually undermine the functional autonomy of the elderly. This article aims to explore and recontextualize the empathic communication practices of caregivers in social nursing homes through an empowerment lens. This research utilizes a qualitative approach, employing in-depth interviews and observations of caregivers and administrators at a social nursing home. The findings indicate that caregivers consistently encourage the elderly to remain independent in their daily activities, a practice interpreted as an attitude of tega. This represents a form of active empathy oriented toward empowerment rather than indulgence. Such communication practices are shown to contribute to the maintenance of physiological self-reliance as well as the psychological well-being of the elderly. This article offers a recontextualization of empathy, shifting from emotional resonance to wisdom in action, while proposing empowerment communication as a contextually grounded empathic framework in the context of geriatric care.